A rare homozygous variant of MC2R gene identified in a Chinese family with familial glucocorticoid deficiency type 1: A case report - Liu, ShuPing; Zeng, Ting; Luo, Cheng; Peng, DanXia; Xu, Xuan; Liu, Qin; Wu, Qiong; Lu, Qin; Huang, FuRong (Frontiers in Endocrinology, 2023)
Background: Melanocortin-2 receptor (MC2R), a member of the G protein-coupled receptor family, is selectively activated by adrenocorticotropic hormone (ACTH). Mutations in MC2R are associated with family glucocorticoid deficiency 1 (FGD1). Case presentation: We first report a Chinese family with two affected siblings with a homozygotic mutation of c.712C>T/p.H238Y in MC2R, presenting with skin hyperpigmentation, hyperbilirubinemia, and tall stature. These individuals showed novel clinical features, including congenital heart defects, not been found in other FGD1 patients. Conclusions: We report a Chinese family with affected siblings having a homozygotic mutation of c.712C>T/p.H238Y in MC2R.Our report may expand the genetic and clinical spectrum of FGD1.